Comparison of spinal cord contusion and transection: functional and histological changes in the rat urinary bladder. (23rd August 2016) - Breyer, Benjamin N.; Fandel, Thomas M.; Alwaal, Amjad; Osterberg, E. Charles; Shindel, Alan W.; Lin, Guiting; Tanagho, Emil A.; Lue, Tom F.
Abstract : Objective: To compare the effect of complete transection (tSCI) and contusion spinal cord injury (cSCI) on bladder function and bladder wall structure in rats. Materials and Methods: A total of 30 female Sprague–Dawley rats were randomly divided into three equal groups: an uninjured control, a cSCI and a tSCI group. The cSCI group underwent spinal cord contusion, while the tSCI group underwent complete spinal cord transection. At 6 weeks post‐injury, 24‐h metabolic cage measurement and conscious cystometry were performed. Results: Conscious cystometry analysis showed that the cSCI and tSCI groups had significantly larger bladder capacities than the control group. The cSCI group had significantly more non‐voiding detrusor contractions than the tSCI group. Both injury groups had more non‐voiding contractions compared with the control group. The mean threshold pressure was significantly higher in the tSCI group than in the control and cSCI groups. The number of voids in the tSCI group was lower compared with the control group. Metabolic cage analysis showed that the tSCI group had larger maximum voiding volume as compared with the control and cSCI groups. Vesicular acetylcholine transporter/smooth muscle immunoreactivity was higher in the control than in the cSCI or tSCI rats. The area of calcitonin gene‐related peptide staining was smaller in the tSCI group than in the control or cSCI groups. Conclusions: Spinal cord transection and contusion produce different bladder phenotypes in rat models of SCI. Functional data suggest that the tSCI group has an obstructive high‐pressure voiding pattern, while the cSCI group has more uninhibited detrusor contractions.